Behavioral ecology: New technology enables a more holistic view of complex animal behavior. - Gail L Patricelli (PLoS Biology, 2023)
As any animal observer will tell you, behavior is complex. A more holistic view of this complexity is emerging as technological advances enable the study of spatiotemporal variability and expand the focus from single components to behavioral systems.